2015
DOI: 10.1007/s00262-015-1746-9
|View full text |Cite
|
Sign up to set email alerts
|

Protamine-stabilized RNA as an ex vivo stimulant of primary human dendritic cell subsets

Abstract: Dendritic cells (DCs) are key in connecting innate and adaptive immunity. Their potential in inducing specific immune responses has made them interesting targets for immunotherapeutic approaches. Our research group was the first to exploit the naturally occurring myeloid DCs (mDCs) and plasmacytoid DCs (pDCs) in therapeutic vaccination trials against melanoma. To develop primary DC subsets as an optimal vaccine, the identification of a clinically applicable adjuvant activating both subsets is required. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 42 publications
2
45
0
Order By: Relevance
“…This analysis suggested that pRNA is potentially a stronger pDC stimulus than FSME, with qualitatively similar effects as indicated by the GO analysis (Table 1). We demonstrated in a previous study that pRNA–induced activation of CD1c + mDCs leads to significantly higher IL12p70 release and a similar TNF-α production as R848 and Poly IC, combined with lower immunosuppressive IL-10 production [30]. The robustness of these findings was corroborated by our functional assays on protein level.…”
Section: Discussionsupporting
confidence: 80%
“…This analysis suggested that pRNA is potentially a stronger pDC stimulus than FSME, with qualitatively similar effects as indicated by the GO analysis (Table 1). We demonstrated in a previous study that pRNA–induced activation of CD1c + mDCs leads to significantly higher IL12p70 release and a similar TNF-α production as R848 and Poly IC, combined with lower immunosuppressive IL-10 production [30]. The robustness of these findings was corroborated by our functional assays on protein level.…”
Section: Discussionsupporting
confidence: 80%
“…Alternatively, both DC subsets can be stimulated with a single TLR agonist. Our group recently established a clinical-grade stimulus that can activate both CD1c + DCs and pDCs in the form of stabilized RNA complexes 43 . The use of such a stimulus would be optimal to exploit the advantages of both DC subsets in a clinical setting.…”
Section: Resultsmentioning
confidence: 99%
“…The most effective response was observed for CD1c + DCs. Notably, CD1c + DCs were the only DC subset that, in response to interaction with platinum-treated tumor cells, secreted TNF-α and IL-10, cytokines typically induced upon exposure to different maturation stimuli 49,50 . This myeloid DC population was capable of engulfing platinum-treated tumor cells, responding to activatory signals and inducing T cell proliferation.…”
Section: Discussionmentioning
confidence: 99%